COVID-19-related knowledge influences mental health, self-care behaviors, and quality of life among elderly with non-communicable diseases in Northern Thailand - Napalai, Pattareeya; Seangpraw, Katekaew; Boonyathee, Sorawit; Ong-artborirak, Parichat (Frontiers in Public Health, 2022)
Background: A growing body of research shows that individuals with non-communicable diseases (NCDs), such as hypertension, diabetes, hypercholesterolemia, and heart disease, are more likely to suffer from severe COVID-19 and, subsequently, death. The purpose of this study was to assess the influence of COVID-19-related knowledge on mental health, healthcare behaviors, and quality of life among the elderly with NCDs in Northern Thailand. Methods: In this cross-sectional study, the participants were 450 elderly people with NCDs, living in the Chiang Rai province, Northern Thailand. Random sampling was applied to select the subjects. Data collection included demographic information, COVID-19-related knowledge, healthcare behaviors, the Suanprung Stress Test-20, the Thai General Health Questionnaire (GHQ-28) for the assessment of mental health, and the Thai version of the World Health Organization Quality of Life-BREF. Results: Almost half of the participants (45.6%) had poor knowledge about COVID-19. More than half of the sample had high stress (52.0%) and a low score in healthcare behaviors (64.9%), while approximately one-third of the participants had mental health problems (34.0%). The overall quality of life during the COVID-19 pandemic was moderate (70.7%). The score of COVID-19-related knowledge was significantly correlated with scores of stress (r = -0.85), mental health (r = -0.74), healthcare behaviors (r = 0.50), and quality of life (r = 0.33). Multiple linear regression found that history of COVID-19 detection and COVID-19-related knowledge were associated with scores of stress and quality of life (p < 0.05). Multiple logistic regression showed that history of COVID-19 detection (OR = 4.48, 95% CI = 1.45 - 13.84) and COVID-19-related knowledge (OR = 0.23, 95% CI = 0.17 - 0.31) were associated with mental health problem (p < 0.05). Discussion: The findings emphasize the importance of COVID-19-related knowledge concerning the improvement of self-care behaviors and quality of life in the elderly population with NCDs during the pandemic, especially due to the high rate of stress and mental health problems documented in our sample. Health education interventions for this vulnerable population should be organized.